Наративні особливості художньої прози Р. Бредбері - Купчишина, Ю. А.; Kupchyshyna, J. A. (Волинський національний університет імені Лесі Українки, 2012)
Статтю присвячено дослідженню основних наративних особливостей та засобів їх реалізації в художніх творах Р. Бредбері. Визначено поняття наративу, образу оповідача (автора), читача, хронотопу та типів оповіді в аспекті очуднення. Розглядаються поняття темпоральної структури тексту та різновиди хронотопу: очуднення часу та очуднення простору. Художній твір класифікується як ієрархічно організована система, основою якої є очуднення – основний композиційний прийом словесного мистецтва. The article deals with the main narrative models and the ways of their realization in Ray Bradbury’s fiction. The concept of narrative, the narrator (the author), the reader, and the types of chronotope are defined. In this paper the interpretation of the types of narration are presented in the aspect of estrangement. The concepts of temporal structure of the text and the types of chronotope: estrangement of time and space are analysed. A work of fiction represents a specific system with its own hierarchy, estrangement is classified as the basic compositional device device of verbal art.
Narrative Features of Ray Bradbury's Fiction
Keywords: наратив; narration; образ автора; the image of the author; висунення; foregrounding